Factors affecting sales workforce retention in banking sector: a study of Maybank Berhad / Ahmad Zefry Abu Sabry, Khairul Izwan Amerruddin and Nornaim Mohamad Halid - Abu Sabry, Ahmad Zefry; Amerruddin, Khairul Izwan; Mohamad Halid, Nornaim (2020)
This study is an attempt to understand the employee retention issue which specifically focusing on sales workforce retention in the banking sector. This is a study of Maybank Berhad which is the leader of banking industry in Malaysia. Employee retention has become a major concern for corporates as survival of organizations was highly dependent on their human-assets. Sales workforce is a bridge gap between customer needs, the product/service and the organisation. Maybank Berhad is currently grappling with the challenges of retaining the right talent of its sales workforce. Hence, the objective of the study is to identify factors affecting sales workforce retention, examine the dominant factors towards retention of sales workforce, and propose strategies that can improve sales workforce retention in Maybank Berhad. Four factors were identified from literature readings and they are flexible working arrrangement, training and development, compensation and benefits, and job and organization fit. The study adopted a survey research design to look at the findings for this research. The population of the study is 3,460 staff. The primary data was collected through closed ended questions with a five point Likert Scale. The study uses purposive sampling technique to capture the response of bankers. A total of 136 respondents successfully gathered by the researchers while the study required 346 of respondents. An alternative method of sample size calculation for multiple regressions was used as suggested by Green (1991) which indicates a minimum sample of 82 should be sufficient for this study. The collected data has been examined and evaluated through Statistical Package for Social Sciences (SPSS). This study concluded that there is a significant relationship between job and organization fit and training and development with sales workforce retention, whereas flexible working arrangement and compensation and benefits have no significant relationship with employee retention. This study was conducted in a particular country and in a particular sector of banking industry, which limits generalization. Possibility of inaccuracy due to the assumption that respondents have the knowledge about their organization structure is the other limitation. It is recommended for future study to focus on retaining the high performer of sales workforce in Maybank.